1981
DOI: 10.1126/science.7466399
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Prevention of Cholesterol Gallstone Formation in Prairie Dogs

Abstract: When prairie dogs (Cynomys ludovicianus) are fed a diet containing cholesterol, a marked increase in gallbladder mucin secretion parallels the evolution of cholesterol supersaturated bile. Gelation of mucin precedes the precipitation of cholesterol liquid and solid crystals and the development of gallstones. Aspirin given to prairie dogs inhibited mucin hypersecretion and gel accumulation and prevented gallstone formation without influencing the cholesterol content of supersaturated bile. This suggests that ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(67 citation statements)
references
References 36 publications
1
66
0
Order By: Relevance
“…In addition to these protective functions, several lines of evidence have shown that gall bladder mucin plays an integral role in the pathogenesis of cholesterol gallstone disease. First, hypersecretion of gall bladder mucin precedes gallstone formation in cholesterol-fed prairie dogs [5] and inhibition of mucin secretion with aspirin prevents stone formation [6]. Secondly, purified human gall bladder mucin accelerates the nucleation of cholesterol crystals in itro in a time-and concentration-dependent manner [7], and thirdly, the presence of mucin within cholesterol gallstones has been demonstrated by electron-microscopic and biochemical techniques [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these protective functions, several lines of evidence have shown that gall bladder mucin plays an integral role in the pathogenesis of cholesterol gallstone disease. First, hypersecretion of gall bladder mucin precedes gallstone formation in cholesterol-fed prairie dogs [5] and inhibition of mucin secretion with aspirin prevents stone formation [6]. Secondly, purified human gall bladder mucin accelerates the nucleation of cholesterol crystals in itro in a time-and concentration-dependent manner [7], and thirdly, the presence of mucin within cholesterol gallstones has been demonstrated by electron-microscopic and biochemical techniques [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Decreasing MUC secretion with aspirin prevents gallstone formation in animal models and decreases the risk of gallstone recurrence following dissolution therapy in humans. 91,92 New progress has been made to identify the initiating event that triggers the observed MUC hypersecretion in recent years. A shift in the bile salt composition toward more hydrophobic, as occurs in lithogenic bile, is more effective at stimulating MUC secretion.…”
Section: Cholesterol Nucleation Promoting and Inhibiting Proteinsmentioning
confidence: 99%
“…Aspirin has been found to reduce mucin gel production in cholesterol-fed prairie dog gall bladder and to inhibit gallstone formation by acting on the mucosal factors of gallstones formation [13]. Aspirin alone does not seem to reduce the prevalence of gallstones disease in a population of regular aspirin users [16] but it can prevent the recurrence of gallstones after oral bile acid dissolution and can reduce gallstone incidence (at a dose of 1000 mg/day orally) in obese patients undergoing rapid body weight loss [16].…”
Section: Expert Opinionmentioning
confidence: 99%
“…The added cholesterol promotes mucin synthesis and secretion in the gall bladder lumen; cholesterol gallstone nucleation from cholesterol monohydrate crystals is observed in the mucus adherent to the gall bladder epithelium, but not in the bulk lumen. Aspirin administered simultaneously in cholesterol-fed prairie dog causes a dose-dependent inhibition of mucin secretion by the gall bladder epithelium and prevents cholesterol monohydrate crystal nucleation and cholesterol gallstone formation also in a cholesterol supersaturated bile [13].…”
mentioning
confidence: 99%